Activity of Adzhams`ka experimental station in the context of the organization of the scientific support of the north stappe of Ukraine (1912-1932 AD) - G. P. Tomashina (History of science and technology, 2018)
In the process of researches, it was established that one of the main premises for the becoming of an agricultural experimental business in the northern part of Kherson province was solving the issue of improving use of lands caused by uncontrolled destruction of virgin lands and non-observance of crop rotations, which affected black soil fertility. Among the main tasks of the Adzhams`ka Experimental Station, which began its activity in 1912, was the search for the best methods of field culture in the conditions of the northern part of the Kherson province. The solution of these problems was carried out by studying the effect of black and cropped fallow on the formation of productivity of grain crops and fodder crops and justifying the optimal time for sowing, seeding rates and applying different doses of organic and mineral fertilizers. It has been established that the distinctive features of activity of the Adzhams`ka Experimental Station from similar research institutions of Ukraine were: a highly specialized areas of ​​researches; a small number of scientific departments and workers; the location of the zone of the northern Steppe of Ukraine on the verge of several large provinces (Kherson, Kiyv, Katery`noslavs`k, Poltava, Podil`s`k), which in the first third of the XX century caused frequent changes in administrative subordination. The scientific work of the Ajamskaya Experimental station was based on the study of the influence on winter, spring and fodder crops of various predecessors, methods and terms of sowing, cropping systems, varietal assortment of agricultural crops. Beside, researches were carried out on the application of organic and mineral fertilizers, were studied the number of little known and infrequent plants , and testing of agricultural machinery and equipment, in particular those produced by the Yelisavetgrad Plant of Elvorti brothers. The main conclusions of the department of field crop cultivation, which were made on the results of the experiments in 1912-1931 became the statement that black fallow was the best way to increase the yield of winter grain crops, despite the fact that the depth of the fallow was not essential for sowing of winter crops, and organic fertilizer was a powerful mean of increasing the yield of agricultural crops. The dissemination and popularization of the research results by the application department of the Adzhams`ka Experimental Station was one of the first steps towards the transfer of agriculture in the region to scientific support.